Collaborative delivery strategies for goods delivery - Karam, Ahmed; Reinau, Kristian Hegner (Proceedings from the Annual Transport Conference at Aalborg University, 2019)
Transportation sector has the highest growth rate of greenhouse gas emissions compared to other sectors. The fact that the current practice of freight transportation strategies is not sustainable in the long run, motivates the urgent need of sustainable transportation strategies with less negative effects on the environment and the society. As one of the possible sustainable solutions, collaborative planning of freight delivery has attracted the interest of professional and scientific communities. This work illustrates some strategies of the collaborative freight transportation.